A Review on Privacy-Preserving Techniques in Data Analytics - Khairul Anuar N.; Abu Bakar A.; Abu Bakar A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Predictive analytics; Privacy-preserving techniques; Data analytics; Privacy preservation; Semi-structured; Structured data; Data Analytics